Factors that Influence the Intention of Micro, Small, And Medium Enterprises (MSMEs) to Use Marketplaces in the Digitalization Era - Suprihatin, Erni; Suhud, Usep; Handaru, Agung Wahyu (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The purpose of this study is to find variables that affect the intention of micro, small, and medium enterprises (MSMEs) to use e-marketplaces. Innovation diffusion theory (IDT) and the technology acceptance model (TAM) are applied in this study to understand how MSMEs adapt to e-marketplaces. While IDT shows how innovation can be accepted and used, TAM shows how MSMEs can accept and use technology through perceived usefulness, perceived ease of use, and attitude characteristics. IDT's approach in this study is limited to compatibility, which is a decisive element in the selection of MSMEs to join the e-marketplace. The perceived trust factor in this study is suggested to support the impact of compatibility on MSMEs' intention to use e-marketplaces. This study uses a survey methodology using questionnaires. A total of 219 samples were taken from MSMEs in Tangerang City, Indonesia, who are at least 17 years old and have previously used the e-marketplace. According to the findings, compatibility significantly influenced the intention to use through perceived trust intervention factors, but the intention to use was not significantly influenced by the intervention variables of attitude, perceived usefulness, or perceived ease of use. The findings of this study have implications for digital marketing plans and strategies for MSMEs and marketplace companies and government policy guidance.